If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + 3 = 54 Reorder the terms: 3 + 3a = 54 Solving 3 + 3a = 54 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 3a = 54 + -3 Combine like terms: 3 + -3 = 0 0 + 3a = 54 + -3 3a = 54 + -3 Combine like terms: 54 + -3 = 51 3a = 51 Divide each side by '3'. a = 17 Simplifying a = 17
| 8(-1+5x)=112 | | 30=9x+y | | x+10-7=4(x+6)-2(3x+3) | | 103-x=2x+6x-7 | | 8w-13w=25 | | 7b^2+-14b+1=0 | | 4x+11=5x-5 | | 4x+8=2x+31+51 | | 12+40=62 | | 3k-1=7x+2 | | 6+2(x+7)=10-3(x-3) | | 40x^2-x+4000=0 | | 5x+11=5x-5 | | 16+8y=48 | | -1+2-(-3)=10 | | -4j=39 | | -34-5x=-12x+64 | | A+2=12 | | 4x+8+2x+3=51 | | -4(x-1)+2x=34+3x | | 7b^2+-14b+7=0 | | -3x-86=-9x+82 | | -7k-2k= | | -6-z=12 | | (4x^2+2)-(2x^2+3)= | | 11x-61=6x+89 | | X^2+4x=44 | | 4(y-4)-8y=20 | | 3(1-7n)= | | r-10=-12 | | x^2+3x=-4(-2x+1)-2 | | 12x-33=3x+75 |